The Pathophysiology of Eosinophilic Esophagitis - Raheem, Mayumi; Leach, Steven T.; Day, Andrew S.; Lemberg, Daniel A. (Frontiers in Pediatrics, 2014)
Eosinophilic Esophagitis (EoE) is an emerging disease characterised by esophageal eosinophilia (>15eos/hpf), lack of responsiveness to acid-suppressive medication and is managed by allergen elimination and anti-allergy therapy. Although the pathophysiology of EoE is currently unsubstantiated, evidence implicates food and aeroallergen hypersensitivity in genetically predisposed individuals as contributory factors. Genome-wide expression analyses have isolated a remarkably conserved gene-expression profile irrespective of age and gender, suggesting a genetic contribution. EoE has characteristics of mainly TH2 type immune responses but also some TH1 cytokines, which appear to strongly contribute to tissue fibrosis, with esophageal epithelial cells providing a hospitable environment for this inflammatory process. Eosinophil-degranulation products appear to play a central role in tissue remodeling in EoE. This remodeling and dysregulation predisposes to fibrosis. Mast cell-derived molecules such as histamine may have an effect on enteric nerves and may also act in concert with TGF-β to interfere with esophageal musculature. Additionally, the esophageal epithelium may facilitate the inflammatory process under pathogenic contexts such as in EoE. This article aims to discuss the contributory factors in the pathophysiology of EoE.